2008
DOI: 10.1073/pnas.0712032105
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid of Rnq1p, the basis of the [ PIN + ] prion, has a parallel in-register β-sheet structure

Abstract: The [PIN ؉ ] prion, a self-propagating amyloid form of Rnq1p, increases the frequency with which the [PSI ؉ ] or [URE3] prions arise de novo. Like the prion domains of Sup35p and Ure2p, Rnq1p is rich in N and Q residues, but rnq1⌬ strains have no known phenotype except for inability to propagate the [PIN ؉ ] prion. We used solidstate NMR methods to examine amyloid formed in vitro from recombinant Rnq1 prion domain (residues 153-405) labeled with Tyr-1-13 C (14 residues), Leu-1-13 C (7 residues), or Ala-3-13 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
130
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 43 publications
9
130
0
Order By: Relevance
“…It is also possible that specific Hsp70/40 pairings might alter prions independently of Hsp104, either directly or through effects on as yet unidentified cellular processes important for prion propagation or that the different Hsp70 isoforms differentially alter expression of other factors that influence prions. Although the fungal prions analyzed to date all have parallel in-register b-sheet structure, different prions, or even strains of the same prions, have different overall conformations and dynamics of growth and replication (Kushnirov and Ter-Avanesyan 1998;Shewmaker et al 2006;Tanaka et al 2006;Baxa et al 2007;Wickner et al 2008). Such conformational differences are likely a basis for differences in how well the chaperone machinery interacts with the different amyloids in vivo and how efficiently it is able to influence dynamics of growth and replication required for prion propagation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that specific Hsp70/40 pairings might alter prions independently of Hsp104, either directly or through effects on as yet unidentified cellular processes important for prion propagation or that the different Hsp70 isoforms differentially alter expression of other factors that influence prions. Although the fungal prions analyzed to date all have parallel in-register b-sheet structure, different prions, or even strains of the same prions, have different overall conformations and dynamics of growth and replication (Kushnirov and Ter-Avanesyan 1998;Shewmaker et al 2006;Tanaka et al 2006;Baxa et al 2007;Wickner et al 2008). Such conformational differences are likely a basis for differences in how well the chaperone machinery interacts with the different amyloids in vivo and how efficiently it is able to influence dynamics of growth and replication required for prion propagation.…”
Section: Discussionmentioning
confidence: 99%
“…A series of two-dimensional 13 C-13 C NMR spectra with 23-, 54-, and 100-ms PARIS mixing were used to probe longer distance 13 C- 13 C contacts (at 17-kHz MAS and 800-MHz 1 H frequencies). To probe the inter-strand register, PITHIRDS-CT measurements (41,42) were carried out using fibrils prepared from Tyr-1-13 CO-labeled dsGB1 at 600 MHz ( 1 H frequency) and an MAS frequency of 20 kHz, with up to 38.4 ms of total dipolar recoupling. Two fibril samples were prepared: one entirely from Tyr-1- 13 CO labeled protein and the other from the same labeled protein diluted 1:2 with unlabeled protein.…”
Section: Methodsmentioning
confidence: 99%
“…Using solid-state NMR, amyloids of the Alzheimer's A␤ peptide and the diabetes-associated amyloid peptide amylin are inregister parallel ␤-sheets (identical residues of different molecules aligned along the fiber long axis) (20)(21)(22) (23)(24)(25). Electron spin resonance studies showed in-register parallel ␤-sheet structures of amylin (26), ␣-synuclein (Parkinson's disease) (27), and Tau (Alzheimer's disease and other 'tauopathies') (28).…”
mentioning
confidence: 99%